Microstructure Analysis, Mechanical Properties And Corrosion Behaviour Of Cryorolled Aluminium 1100 Alloy With Different Heat Treatment - Zakaria, Siti Aminah (2018)
The present work investigated the microstructure, mechanical properties and corrosion behavior of cryorolled Al 1100 alloy in various pre-heat treatment. Before subjecting to cryorolling process, three different pre-heat treatment were selected; non pre-heat treatment, annealing (200˚C- 400˚C) and solution treatment (500˚C-580˚C). Pre-annealed sample at 250˚C and pre-solution treated sample at 540˚C showed the highest grain aspect ratio. Both of the samples also showed the smallest crystallite size (37.53 nm, 46.52 nm) and the highest lattice strain (9.50×103, 9.02×10-3). Pre-annealed cryorolled sample also resulted in higher hardness, ultimate tensile strength and yield strength with an improvement of 43.44%, 24.64% and 20.33% respectively. The improvement of hardness, tensile strength and yield strength were achieved for pre-solution treated cryorolled sample at 540˚C with increment of 16.93%, 1.20% and 5.6% respectively. The hardness and tensile strength after post annealed gradually decreased, but ductility increased for both samples. Cryorolled pre-treatment samples after post-annealed at 175˚C showed a high density of dislocations with formation of new sub-grains structure. Both of the pre-heat treatment cryorolled sample exhibited higher corrosion resistance with the lowest corrosion rate 0.0214mm/year and 0.0272mm/year and corrosion current 1.30μA and 2.14 μA, and more positive value of corrosion potential -0.7970V and -0.9774V for pre-annealed cryorolled and pre-solution treated sample respectively. Overall, the pre-annealed at 250˚C cryorolled sample followed by post-annealed B1reatment at 175˚C has shown the best value (mechanical and corrosion behaviour) in general.